MyLexics: An assistive courseware for dyslexic children to learn basic Malay language - Abdullah, Muhammad Haziq Lim; Hisham, Syariffanor; Parumo, Shahril (New York, United States, 2009)
Dyslexia is a language-based learning disability resulting in people experiencing difficulties in reading, spelling, writing and speaking due to inability to differentiate sound components. These problems are sometimes accompanied by short-term memory difficulties, a lack of organizational skills and time management issues which all have an impact on learning. Dyslexia can occur regardless of age groups and in some cases; dyslexics may have higher IQ level compare to others.